EFEKTIVITAS PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENURUNAN MUAL MUNTAH PADA IBU HAMIL DENGAN EMESIS GRAVIDARUM TRIMESTER I DI PMB MUSDALIFAH: The Effectiveness Of Administration Of Lavender Aromatherapy To Reduce Nausea, Vomiting In Pregnant Women With Emesis Gravidarum I Trimester At Pmb Musdalifah - Vivi Vitriani Setianingrum (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
The first trimester is an important period in pregnancy, because at this time the formation of organs including the fetal brain occurs. In some pregnant women have problems meeting their nutritional needs, which is caused by nausea and vomiting in early pregnancy. This study aims to determine the effectiveness of giving lavender aromatherapy to reducing nausea and vomiting in pregnant women with first trimester emesis gravidarum at PMB Musdalifah. This type of research uses a quasi-experimental method with a pretest - posttest approach with a control group design. This study consisted of 2 groups, where 1 group was the control group and 1 group was the intervention group that was given lavender aromatherapy. The population of this study were 48 pregnant women at PMB Musdalifah. As for the sampling technique using purposive sampling. The sample in this study were 32 respondents who were divided into 2 groups with a ratio of 1:1. Data processing uses editing, coding, scoring, tabulating with Mann Whitney data analysis. It can be concluded based on the results of hypothesis testing showing a p value of 0.045 (p value <0.05) so that Ha is accepted. There is the Effectiveness of Giving Lavender Aromatherapy to Reducing Nausea Vomiting in Pregnant Women with Emesis Gravidarum Trimester I at PMB Musdalifah. Based on the above conclusions, it is expected to increase the participation of pregnant women to use non-pharmacological treatments such as lavender aromatherapy.